Perceived family relationships and social participation through sports of urban older adults living alone: An analysis of the mediating effect of self-respect levels - Zhou, Rong; Cui, Jinghang; Yin, Xingxing (Frontiers in Public Health, 2023)
The perception of good family relationship is an important factor to promote social participation through sports (SPS) of older adults living alone. Based on the survey data of 2,801 older adults living alone in Chengdu, Shanghai, Guangzhou, Hohhot, and Dalian, the quantitative index of their “ac-tiveness in SPS” was constructed. The OLS model, the Ologit model, the instrumental variable method and the mediating effect were used to explore the influence mechanism of perceived family relation-ships of urban older adults living alone (UOALA) on their SPS. The results demonstrate that: (1) UOALA's activeness in SPS in China is generally at a low level; (2) perceived family relationships have an impact on UOALA's activeness in SPS, i.e. positive family relationships will increase their activeness in SPS, and there are evident gender differences in this tendency; (3) there are regional differences in the activeness in SPS among the older adults living alone in urban areas, and perceived family rela-tionships in first-tier and second-tier cities have a more significant impact on their activeness in SPS; (4) the mediating effect analysis shows that perceived family relationships can indirectly promote urban old people’s activeness in SPS through the reconstruction of their self-respect, and this is more pro-nounced in women. Therefore, the important role of families cannot be ignored in promoting SPS of the older adults. Keywords: urban older adults living alone (UOALA); perceived family relationships; social participa-tion through sports (SPS); self-respect level; the mediating effect